Republic of Estonia : Selected Issues. (IMF Staff Country Reports; Country Report, 2017)
This Selected Issues paper examines the impact of fast unit labor cost (ULC) growth in Estonia. ULCs in Estonia have now reached a level at which further unmitigated wage growth risks material damage to competitiveness and income convergence prospects with western Europe. This highlights the importance of making Estonia's pro-productivity policies a success, but in the nearer term the onus is on mitigating excessive wage growth because in this area, Estonia, together with the other Baltics, distinguishes itself from the rest of central and eastern Europe. Tax policy can provide short-term relief.